Quantifying the Impact of Cereal Price Changes on Food Security in Tunisia: A Panal Threshold Regression Model - Gannoun, Ibtissem; Liouane, Naoufel; Jammali, Dorsaf; Jenana, Hassen Ben (International Journal of Economics and Financial Issues, 2025)
This study examines the relationship between cereal price volatility and food security in Tunisia from 1991 to 2021 using a Panel Threshold Regression (PTR) model. The findings reveal a significant regime shift at a cereal price index of 4.6131, delineating low- and high-price regimes. Results show that rising cereal prices negatively impact food security but to a lesser extent during high-price volatility periods, highlighting the importance of ingrained consumption patterns and government interventions, such as subsidies. GDP per capita, real effective exchange rate, and external debt show varying influences across regimes. The study recommends diversifying import sources, enhancing local agricultural productivity through sustainable practices, and improving debt allocation efficiency. Policymakers should focus on price stabilization, targeted subsidies, and trade competitiveness to strengthen food security and resilience. The study underscores the need for comprehensive strategies addressing structural vulnerabilities and fostering long-term sustainability in Tunisia’s food system.